Metaphors in the Muspilli. - Boyer, Tina Marie (Neophilologus, 2024)
This study delves into the metaphorical nature of the OHG Muspilli. Employing cognitive linguistics, the research aims to explore the deeper implications of metaphors, which are believed to be deeply ingrained in our thought processes and reasoning about the world. According to Lakoff and Johnson's theory, metaphors are more than just linguistic tools; they are integral to understanding and interacting with the world around us. Moreover, the meaning of language is not solely determined by individual words or grammar but is also shaped by the social and cultural context in which it exists. The poet and their work are intertwined in a syncretistic world where diverse cultural expressions converge. In this context, the Muspilli becomes a center for religious syncretism, where metaphors of the older belief system intersect with those of the newer one. As a place of "polyvocality," it seeks to be didactic, shedding light on the complex interplay between language, culture, and religion. Overall, this research offers a nuanced understanding of the OHG Muspilli, revealing its significance as a cultural artifact.